Sliding Contact Fatigue Damage of Metallic Implants in a Simulated Body Fluid Environment - Mihir V. Patel; Edward Cudjoe; Jae Joong Ryu (Lubricants)
At the modular interface of the joint implants, repeated contact stresses in a corrosive synovial environment cause surface degradation that worsens over time. The lubricating mechanisms at the joints are altered by the deteriorated synovial fluid by the wear debris and corrosion products. As a result, the joint implants’ unsatisfactory performance will be exacerbated by the synergistic combination of wear and corrosion. In this work, reciprocal sliding contact tests in simulated synovial fluid were conducted on the two main metallic implant materials, CoCrMo and Ti6Al4V. The mechanical and electrochemical reactions were described by monitoring the open-circuit potential (OCP) and coefficient of friction (COF). The electrochemical damage that altered the oxidation chemistry on both surfaces was illustrated by the potentiostatic test findings. The surface damage process of CoCrMo under all contact loads presented unstable chemomechanical responses. On the other hand, the Ti6Al4V results revealed a moderate decrease in fretting current and stable changes in the coefficient of friction. Consequently, the experimental investigation determined that, when mechanical loadings and electrochemical stimulus are combined, Ti6Al4V’s biocompatibility would be superior to CoCrMo’s.